'Imagine talking about politics in a kids' game': Making sense of #BLM in Nintendo's Splatoon 2. (August 2022) - Mee, David; Jackson, David
On Twitter and other established digital social networks, references to the Black Lives Matter movement almost doubled after George Floyd's murder (see Giorgi et al., 2020, 'Twitter corpus of the #blacklivesmatter movement and counter protests: 2013 to 2020'), alongside a similar rise in references to the counter-protest terms 'All Lives Matter' and 'Blue Lives Matter'. Around the same time, the authors found online players of Splatoon 2 (Nintendo) expressing Black Lives Matter sentiments when using in-game design tools. These messages quickly disappeared in the game space to be replaced by longer-lived political content relating to LGBTQ+ activist sentiments and other non-political messaging. This visual essay provides documentation of memes captured by one of the authors between 6 and 14 March 2020 and discussion of their significance as data. The authors conclude that, despite being digital artefacts, Splatoon posts may be better understood using Cramer's 'What Is "Post-digital"' (2014) reading with different characteristics from normal digital activism artefacts. The visual form attempts to underline the visual character of these post-digital artefacts, which contain no machine-readable textual content or metadata. Nevertheless, they represent a form of community discourse that is little examined and that the authors suggest should be documented and researched despite its awkward data structure.